Particle flux data from the expedition ARTofMELT, Arctic Ocean, 2023 - Theresa Mathes; Andreas Held (PANGAEA, 2025)
In spring 2023, near-surface particle and heat fluxes were measured using the gradient method during the ARTofMELT Arctic Ocean Expedition aboard the icebreaker Oden. The gradient system was used to measure the number of particles, temperature and wind speed at five different heights close to the surface. We divided the surface conditions into three categories: open water, open lead and closed ice. We calculated the sensible heat flux (HF) and the particle flux (PF) based on the flux-gradient relationships method. Monte Carlo simulation was utilized to estimate the uncertainty of the flux estimate due to the error of the measuring instruments.
In: Mathes, T; Held, A (2025): Particle flux-gradient relationships for the expedition ARTofMELT, Arctic Ocean, 2023 [dataset bundled publication]. PANGAEA, https://doi.pangaea.de/10.1594/PANGAEA.974992 (DOI registration in progress)